An unusual pattern of limb morphology in the Tithonian marine turtle Neusticemys neuquina from the Vaca Muerta Formation, Neuquén Basin, Argentina - de la Fuente, Marcelo Saul (2011)
Here, we report an unusual pattern in the manus and pes morphology of the Tithonian marine turtle Neusticemys neuquina. We analyse the forelimbs of two previously known specimens and describe the hind limbs of two previously undescribed specimens. Neusticemys neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. specimens and describe the hind limbs of two previously undescribed specimens. Neusticemys neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. Neusticemys neuquina. We analyse the forelimbs of two previously known specimens and describe the hind limbs of two previously undescribed specimens. Neusticemys neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. Neusticemys neuquina is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. is characterized by a relative elongation of both the forelimb and hind limb, compared with stem Chelonoidea, as well as an elongation of the pedal digit V, achieved through the elongation of the bones, as well as a moderate hyperphalangy. The elongation of pedal digit V is the most striking feature of N. neuquina, a feature unknown in other turtles. unknown in other turtles. N. neuquina, a feature unknown in other turtles.